Pembelajaran daring materi ruas garis bangun datar dan bangun ruang pada siswa kelas 2 SDN 243 Cicabe dengan pendekatan realistik berbantuan video - Herlina, Elin; Kelana, Jajang Bayu (IKIP Siliwangi, 2024)
This study aims to examine the online learning about two dimentional and three dimentional shapes for second grades of SDN 243 Cicabe, using a realistic approach with video assistent. The method for this study is descriptive qualitative. Subjects of this study is 2nd grade students from SDN 243 Cicabe Bandung with a total of 25 students consisting with 14 male students and 11 female students. The instruments for this study is using abservation sheets, question about two dimentional and three dimentional shapes, and interview questionaries for students. The result show there was an increase for the quality of learning when was realistic approach were used. Its shown with the average point of two dimentional and three dimentional shapes material is 73 and its classified as good the higest is 95, and the lowest is 40. The completion for the test show 72% student get a score above the minimum criteria, and 28% student still get bellow the minimum criteria.